Nutritive Value of Wheat Bran Diets Supplemented With Fresh Carrots and Wet Brewers' Grains in Yellow Mealworm. Issue 3 (13th May 2022) - Fasce, B; Ródenas, L; López, M C; Moya, V J; Pascual, J J; Cambra-López, M
Abstract: We evaluated the effect of supplementation of a wheat bran (WB) diet with fresh carrots (FC) or wet brewer's grains (WBG) on the growth performance and chemical composition of Tenebrio molitor larvae. Additionally, a digestibility trial was performed to determine the nutritional value of the raw materials used. The control diet was based on WB-only. Two other diets were formulated in which WB was supplemented with FC (FC diet) or with WBG (WBG diet). The experiment was conducted in trays (12 per treatment) and lasted 90 d. Larval weight, feed intake, and excreted feces were controlled in each tray the experiment. The digestibility trial was performed from 48 to 62 d post-hatch. Results showed digestibility coefficients of ashes, crude protein, and gross energy were significantly higher in FC diet compared with the other diets. Consequently, both digestible energy (DE) and digestible protein (DP) contents of FC were also significantly higher than those obtained for WB and WBG diets (on av. +1.12 megajoule [MJ] DE and +9.15 g DP per kg dry matter [DM]; P < 0.003). Mealworms fed FC diet showed significantly higher final weight and average daily gain than those fed the WBG diet (+12.4%), being higher in WBG than in WB diet (+3.5%). Dietary treatment did not affect DM, ashes, ether extract, and crude protein content of mealworms obtained. Some dietary effects on amino acid and fatty acid composition were observed. This study provides novel data and a unique experimental approach to assess the nutritional value of raw materials in mealworms.